The 3' region of the chicken hypersensitive site-4 insulator has properties similar to its core and is required for full insulator activity. - Paritha I Arumugam; Fabrizia Urbinati; Chinavenmeni S Velu; Tomoyasu Higashimoto; H Leighton Grimes; Punam Malik (PLoS ONE)
Chromatin insulators separate active transcriptional domains and block the spread of heterochromatin in the genome. Studies on the chicken hypersensitive site-4 (cHS4) element, a prototypic insulator, have identified CTCF and USF-1/2 motifs in the proximal 250 bp of cHS4, termed the "core", which provide enhancer blocking activity and reduce position effects. However, the core alone does not insulate viral vectors effectively. The full-length cHS4 has excellent insulating properties, but its large size severely compromises vector titers. We performed a structure-function analysis of cHS4 flanking lentivirus-vectors and analyzed transgene expression in the clonal progeny of hematopoietic stem cells and epigenetic changes in cHS4 and the transgene promoter. We found that the core only reduced the clonal variegation in expression. Unique insulator activity resided in the distal 400 bp cHS4 sequences, which when combined with the core, restored full insulator activity and open chromatin marks over the transgene promoter and the insulator. These data consolidate the known insulating activity of the canonical 5' core with a novel 3' 400 bp element with properties similar to the core. Together, they have excellent insulating properties and viral titers. Our data have important implications in understanding the molecular basis of insulator function and design of gene therapy vectors.